Contribution towards a Grass Flora of Anantapur District Andhra Pradesh - Pullaiah, T. (Indian Forester, 1986)
In the present paper an account of grass of Anantapur district of Andhra Pradesh (13Â°41’- 15Â°14’ and 76Â°4’7 - 78Â°l6’ E) made during the years 1979-84 is given, 93 species belonging to genera have been recorded from the district. The distribution of the grasses and the vernacular names are given. Diectomis fastigiata is a new record for south India while Paspalum distichum and Rhynchelytrum repents are new records for the state of Andhra pradesh.